Challenges in diagnosis and treatment refractory neonatal seizures in immature brain - Palic, Ilija G.; Rakic, Olgica P. (International Journal of Research in Medical Sciences, 2025)
Seizures are the most common clinical signs of neurologic dysfunction in neonates. The risk for seizures is inversely related to gestational age and birth weight. Several factors contribute to excessive excitation in the immature brain, such as depolarizing action of γ-aminobutyric acid, change of the subunit composition of the glutamate receptors and incomplete glial clearance of glutamate and potassium. Continuous EEG is the gold standard for diagnosing neonatal seizures. However, video EEG recording has several limitation, especially in preterm neonates. In recent years, amplitude-integrated EEG has been used to detect electrographic seizures. In accordance with the current recommendations, if neonatal seizures do not stop to phenobarbitone, levetiracetam or phenytoin may be used as a second-line anti-seizure medications, as well as midazolam or lidocaine. Midazolam is recommended in the treatment for refractory seizures in neonates requiring mechanical ventilation. In this report, we present a diagnostic and treatment dilemmas of refractory seizures in extremely preterm neonate.